2010
DOI: 10.3168/jds.2008-1831
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Northeast dairy industry: Large-scale modern confinement feeding and management-intensive grazing

Abstract: This paper provides a summary of results from a recent survey of 987 dairy farmers in 4 northeastern US states. The survey results provide descriptive characteristics of the current state of dairy farming in the region, as well as farmer satisfaction levels, concerns, and plans for the future of their farming operations. The paper analyses characteristics of two increasingly important dairy production systems used in the Northeast. Averages from across the survey states (Maryland, Pennsylvania, New York, and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…Agriculture in the United States is certainly different than it was a century ago-many producers have abandoned diversified farming with numerous crops, grazing livestock, and managed woodlands for an industrial model based on specialization of a few crops if land were available or large confined animal feeding operations if land were limiting (Winsten et al 2010;Nelson et al 2012). Nearly 80% of US beef producers have a herd size of <50 head, and 76% of dairy producers have a herd size of <100 head (USDA NASS 2011).…”
Section: Liability Assetmentioning
confidence: 99%
“…Agriculture in the United States is certainly different than it was a century ago-many producers have abandoned diversified farming with numerous crops, grazing livestock, and managed woodlands for an industrial model based on specialization of a few crops if land were available or large confined animal feeding operations if land were limiting (Winsten et al 2010;Nelson et al 2012). Nearly 80% of US beef producers have a herd size of <50 head, and 76% of dairy producers have a herd size of <100 head (USDA NASS 2011).…”
Section: Liability Assetmentioning
confidence: 99%
“…Dairy farms rely heavily on fossil energy inputs like fuel, fertilizers, herbicides, and pesticides, which contribute directly to greenhouse gas (GHG) levels in the atmosphere (Robertson et al, 2000;Cruse et al, 2010;Woodhouse, 2010;Gelfand et al, 2010;Davis et al, 2012). For several decades the number of dairy farms in this region has been decreasing, bifurcating into both larger consolidated operations as well as smaller owner-operated farms (Winsten et al, 2010). At the same time there has been an increase in specialized crop farms without animals, while livestock farms are housing more animals on smaller areas of land.…”
Section: Introductionmentioning
confidence: 99%
“…The rotation of the animals through the sections allows the grazed sections to regrow before re-grazing and because the grazing period in each section is very short, severe treading and overgrazing is avoided resulting in reduced P losses. A survey the North-eastern United States showed that 13% of the dairy producers use this method with the number of farms using the system increasing (Winsten et al, 2010). The system was typically used by small or medium size herds (50 to 70 animals), because it is labour-intensive.…”
Section: Rotational Grazingmentioning
confidence: 99%
“…The system was typically used by small or medium size herds (50 to 70 animals), because it is labour-intensive. Producers using the system had better economic and environmental advantages than producers using traditional systems for dairy cattle (Winsten et al, 2010). Haan et al (2006) compared the effect of rotational stocking to a residual sward height of 5 or 10 cm with continuous stocking and ungrazed pastures.…”
Section: Rotational Grazingmentioning
confidence: 99%